2021
DOI: 10.1017/s0033291721000404
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of adherence to group interventions in psychosis: do people attend?

Abstract: Background Evidence supports the use of group therapy for symptom reduction and improving functioning in people with psychosis. However, research guidelines highlight the importance of establishing the feasibility of interventions. Adherence is an important indicator of feasibility and an essential step in supporting the development of the evidence base for group interventions. This review aims to estimate adherence, and possible barriers and facilitators, to psychotherapeutic groups in people with psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…The present study primarily investigated therapy adherence and safety, which are both aspects of feasibility, and showed that the mean percentage of attendance at therapy sessions in the whole group of participants is 77 %. This result is consistent with a large systematic review by Sedgwick et al (2021) , in which the mean percentage of therapy adherence to various group interventions for the treatment of psychosis was 76.4 % (SD = 17.4).…”
Section: Discussionsupporting
confidence: 90%
“…The present study primarily investigated therapy adherence and safety, which are both aspects of feasibility, and showed that the mean percentage of attendance at therapy sessions in the whole group of participants is 77 %. This result is consistent with a large systematic review by Sedgwick et al (2021) , in which the mean percentage of therapy adherence to various group interventions for the treatment of psychosis was 76.4 % (SD = 17.4).…”
Section: Discussionsupporting
confidence: 90%
“…This evaluation was conducted in routine clinical practice and found that a brief DBTinformed group for individuals with established psychosis was feasible and acceptable (uptake, completion, service-users' views) and associated with potential clinical impact (pre-post outcome measures). Rates of uptake were around 80%, with nearly 80% of those completing, comparing favorably to other group interventions for psychosis (Sedwick, Hardy, Newbery, & Cella, 2021). Service users reported high satisfaction and valued outcomes, including increased emotional awareness, understanding and acceptance, selfefficacy in relation to managing emotions, and pursuit of valued activities.…”
Section: Discussionmentioning
confidence: 94%
“…45 Finally, the specifics of intervention delivery (e.g., individual vs group format) could impact engagement/adherence. 86 Further research is needed to clarify which and how intervention characteristics influence participant engagement.…”
Section: Suggestions For Future Researchmentioning
confidence: 99%